Experimental investigation of R.C. slabs with increased covers and resulting crack widths - Murty, D. Sree Rama Chandra; Satyanarayana, C. (Journal of Structural Engineering, 2025)
IS 456 : 2000 is the most influential code in India, and plays a leading role in many ways related to concrete and reinforced concrete, including education, design, production, construction and repair. Continued research focusses on gaps in knowledge, and the research findings renovate, or alter existing codal provisions or add new provisions to raise the whole concrete industry to a higher and newer level of performance. A test programme was initiated to investigate the influence of increased concrete covers in reinforced concrete slabs, stipulated in the IS 456 : 2000, on the development of crack widths. The reported test results show that mere adoption of detailing of steel reinforcement as specified in the code, ensuring durability, relative to crack growth is not totally valid.